O desempenho escolar em ciências e o pluralismo epistemológico : a elaboração de questões do eixo temático "Vida e Ambiente" - Cunha, Camila (2016)
The quality of basic education is measured through school performance tests on a large scale and, from other information, build an overview about the situation of the Brazilian educational. However, despite of the complex evaluation system to which basic education is submitted, science education is still rarely addressed in large-scale assessments. It is also noticeable in the State of Sergipe the lack of own assessment systems, especially compared to other states that have consolidated their systems for several years. With regard to science education, we share the idea of epistemological pluralism, which admits in school structures the appreciation and respect for different forms of knowledge, by also believe that such worldviews are as appropriate as scientific knowledge, each in its areas of school performance. Performance evaluations that are able to share an epistemological pluralist vision are essential to understand what knowledgeb the students use to solve conceptual problems in science. Starting from the construction of a performance test in science with differentiated structure of existing ones, our research sets in order to look for alternatives in building assessment tools of science education. The development of the research was divided into stages, including: reference matrix, scale for construction issues, development issues, validation issues, pilot application and final application. The reference matrix was constructed based on the interests of three groups: the state, teachers and students. Each step has elucidated aspects related to science content taught in the thematic area “Life and Environment". The school performance, even when measured by different instruments, is strongly influenced by social position and economic conditions of the family, as apparent in the correlations made by this study. For the axis "Life and Environment" most students explain the concepts of nature for an alternative bias to the science, it is considered what is expected of them at the basic level. Some concepts have greater resistance to learning than others, such as the origin of life and global warming, probably being influenced by factors outside the classroom, such as religion and the media. Others are more accepted by students and are closer to the reference knowledge, such as the concepts of ecology, botany and biodiversity.